Survival Status and Predictors of Mortality Among Asphyxiated Neonates Admitted to Jimma University Medical Center, Southwest Ethiopia: A Retrospective Cohort Study - Lencho Kajela solbana; Solomon Berhanu; Yenealem Gezahegn; Guta Kune (Health Science Reports)
ABSTRACT Background and Aims Perinatal asphyxia is the second leading cause of neonatal mortality in sub‐Saharan African countries, including Ethiopia. This study aimed to assess survival status and predictors of mortality among neonates admitted to Jimma University Medical Center with perinatal asphyxia. Methods A retrospective cohort study was conducted on 373 asphyxiated neonates admitted to Jimma University Medical Center from April 12, 2019, to May 5, 2022. Data were collected from May 18 to June 3, 2022, entered into Epidata version 3.1, and analyzed using R software version 4.2.1. On univariate Cox regression, variables with a p < 0.25 were selected for the final model. Multivariate Cox regression was used to identify significant predictors of mortality among asphyxiated neonates at a 0.05 level of significance and a corresponding 95% confidence interval of the adjusted hazard ratio. Results The median survival time of the participants was 20 (95% CI: 18–23) days. During 2888 days of total person‐time at risk, a 29.09 (95% CI: 23.20–36.01) per 1000 person‐days incidence rate of neonatal mortality was identified. The significant predictors of mortality were stage III Hypoxic ischemic encephalopathy (AHR: 3.46, 95% CI: 1.55–7.70), acute kidney injury (AHR: 2.82, 95% CI: 1.28–6.23), and stress ulcers (AHR: 2.24, 95% CI: 1.26–3.97). Conclusion The incidence of mortality was relatively high among the study participants. Stage III Hypoxic ischemic encephalopathy, acute kidney injury, and stress ulcers were significant predictors.